Time and the Locust Plagues in the Book of Joel and the Sefire Inscriptions - Scott, Kevin (The catholic biblical quarterly, 2023)
In this article, I argue that reading the locust plagues of Joel and Sefire intertextually adds fresh insights to the interpretation of the function of time in both texts. In Joel, the prophet utilizes an indeterminate number of years when referring to the destruction of the locust plague to highlight the limited nature of the destruction caused by the plague and to encourage the community to hope in the approaching restoration of the land. In the Sefire inscriptions, Bar-Ga’yah calls for a seven-year locust plague to signal to Mati‘el that his land will have no hope of material prosperity or survival if he breaks the treaty. Narratives of locust plagues depict an experience common to all people in the ancient Near East, and these texts highlight the adaptability of this common image. Locusts can incite terror in communities, but they can also function as harbingers of hope.